If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4cos(2x) = 8sin(x) * cos(x) Remove parenthesis around (2x) 4cos * 2x = 8sin(x) * cos(x) Reorder the terms for easier multiplication: 4 * 2cos * x = 8sin(x) * cos(x) Multiply 4 * 2 8cos * x = 8sin(x) * cos(x) Multiply cos * x 8cosx = 8sin(x) * cos(x) Multiply ins * x 8cosx = 8insx * cos * x Multiply insx * cos 8cosx = 8cinos2x * x Multiply cinos2x * x 8cosx = 8cinos2x2 Solving 8cosx = 8cinos2x2 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-8cinos2x2' to each side of the equation. -8cinos2x2 + 8cosx = 8cinos2x2 + -8cinos2x2 Combine like terms: 8cinos2x2 + -8cinos2x2 = 0 -8cinos2x2 + 8cosx = 0 Factor out the Greatest Common Factor (GCF), '8cosx'. 8cosx(-1insx + 1) = 0 Ignore the factor 8.Subproblem 1
Set the factor 'cosx' equal to zero and attempt to solve: Simplifying cosx = 0 Solving cosx = 0 Move all terms containing c to the left, all other terms to the right. Simplifying cosx = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Subproblem 2
Set the factor '(-1insx + 1)' equal to zero and attempt to solve: Simplifying -1insx + 1 = 0 Reorder the terms: 1 + -1insx = 0 Solving 1 + -1insx = 0 Move all terms containing c to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -1insx = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -1insx = 0 + -1 -1insx = 0 + -1 Combine like terms: 0 + -1 = -1 -1insx = -1 Add 'insx' to each side of the equation. -1insx + insx = -1 + insx Combine like terms: -1insx + insx = 0 0 = -1 + insx Simplifying 0 = -1 + insx The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| f+3f-2f=6+6+6 | | 10n^2=8n+7 | | (x+4)(x-5)(x+6)(x-7)=504 | | 9k-8k+7k=56 | | 12-16a=-5a^2 | | 7t-3t-3t=8-7 | | 5r^2-20=-r | | 8u+2u=44-4 | | 5x^2+23x-2=0 | | 19t+36=6t^2 | | 19+36=6t^2 | | 4x^2-n+12=0 | | 5m+m=39-9 | | 5*111+5-5=555 | | 1n^2-1n+12=0 | | 5x+5-5=555 | | n^2-1n+12=0 | | 5x+5+5=555 | | y=3x^2+4x+4 | | 4k+3k=84 | | 5*108+5+5=555 | | -2x^2+3x+7=0 | | 11x-(-3)=-19 | | 11n^2+n-11=0 | | 5x+5+5+5=555 | | -2-7x+x=-38 | | 84=7-7h | | p^2-32=4p | | 2lnx-ln(x+1)=3 | | 5n^2+6n-32=0 | | 180=42+(x+8) | | 180=57+(x+23) |